To the independent freeholders and freemen, of this city and county : It having been industriously propagated, that numbers of the voters of this city and county, have been long intimidated at elections . - Hardenbrook, Abel ([publisher not identified], 1770)
Calling a meeting to discuss voting by secret ballot.